Cooperative Binding of SRSF3 to Structured 3’ss-α Exon RNA during α Exon Inclusion in the ZO-1 mRNA - Tea Anastasia Ruiz-Luis; Carlos Ortuño-Pineda; José Manuel Galindo-Rosales; Odila Saucedo-Cárdenas; Jesús Valdés (Current Issues in Molecular Biology, 2023)
ZO-1α+ and ZO-1α− proteins are expressed in hermetic and leaky tight junctions, respectively. Two cis-acting distant exonic elements partly activate the 240 nucleotide-long α exon producing the ZO-1α+ isoform. However, the elements within and around the α exon and their respective factors involved in its splicing are unknown. To study the dynamic interaction between SRSF3 and its bioinformatically predicted target sites around the 3’ss upstream of the α exon during its activation, we performed EMSA, crosslinking, and in vivo splicing assays by ZO-1 minigene expression and siRNA-mediated silencing in transfected cells. Using V1 RNase, we probed the possible formation of a hairpin RNA structure between the intronic and proximal exonic SRSF3 binding sites. The hairpin sufficed for complex formations in the EMSA. The interaction of SRSF3 with the intronic site promoted the cooperative binding of SRSF3 to the exonic site. Finally, SRSF3 restored α exon activation in SRSF3 knockdown transfectants. Altogether, our results show that SRSF3–hairpin RNA interaction is crucial in the early recognition of 3’ss for α exon activation. It remains to be explored whether SRSF3 recruits or stabilizes the binding of other factors or brings separate splice sites into proximity.